Enhanced inverter switching for fast response direct torque control [of induction motor drives]. - Purcell, A. (IEEE Transactions on power electronics)
In classical direct torque control (DTC), an inverter switching event can occur once in each control update period. Because the nature of the inverter switching event is unconstrained, it is essential to limit the inverter switching frequency, and hence the control update period, to ensure that under no circumstances is the allowable switching frequency of any individual power device exceeded. Consequently the switching capability of individual power devices is generally under-utilized, and the control scheme produces high levels of ripple in the motor current and torque. This paper describes a new strategy for device switching and voltage vector selection in DTC. The basis of the strategy is an increase in the control update frequency, while limiting the switching rate of each inverter leg. Although the rate at which device switching events may occur is unchanged, the higher control update frequency leads to higher resolution timing of switching events. The advantages of the strategy, demonstrated by experimental results on a 3 kW induction motor drive, are a significant reduction in the steady-state torque ripple as well as a faster transient response